Human resource evaluation using a GRA-based decision model in an interval-valued fuzzy environment - Seyed Mahdi Ghanizadeh (تصمیم گیری و تحقیق در عملیات)
Purpose: This research aims to present a new hybrid method for evaluating and choosing the right human resources for the right position in the organization under conditions of uncertainty.Methodology: In this research, the Grey Relationship Analysis (GRA) method developed with positive and negative ideal concepts is used to evaluate the employees and human resources of organizations and put the right person in the right position. Also, the best-worst method is used to evaluate the effective criteria in human resource evaluation. Finally, the two presented methods are developed in the interval-valued fuzzy environment for facing uncertainty.Findings: The proposed method was successfully applied to the problem of evaluating human resources in an environment of uncertainty. Also, according to the best-worst method, it was found that the knowledge and experience of the person are very important and have the most weight. Finally, using the developed GRA method, it was determined that person number 3, among five candidates, is suitable for managing systems and methods in the organization.Originality/Value: In this research, the GRA method is improved based on positive and negative ideal concepts and developed in an interval-valued fuzzy environment. Then, the developed BWM method under an interval-valued fuzzy environment is used to weigh important criteria in the personnel evaluation process. Interval-valued fuzzy sets provide more degrees of freedom for real-world uncertainty due to having interval membership degrees. Finally, the position of systems and methods manager, a new organisational job, has been examined.